Conceptualising the interaction among organisational factors towards internal control quality - Alazzabi, Waled Younes; Mustafa, Hasri; Issa, Mohamed (Emerald Group Publishing, 2021)
Purpose: This paper provides a theoretical foundation and conceptual framework to explain the interactions among risk management (RM), top management support (TMS), and internal audit activities (IAA) to achieve internal control quality (ICQ). Design/methodology/approach: A review of the extant literature in RM, auditing and management control is conducted to develop and establish theoretical relationships. Findings: In this work, interconnectedness among organisational factors is discussed by drawing on contingency theory to provide the theoretical logic and support the conceptual framework. Research limitations/implications: Although this work illustrates the significance of the moderation effect of TMS and the mediation effect of IAA to link RM processes with the quality of internal controls, limitations exist, as the study is conceptual and lacks empirical evidence. The paper emphasises education and training on RM and internal audit to address emerging issues and arising challenges in RM and ICQ. Originality/value: The paper extends the existing literature in the area of ICQ, which is discussed extensively in developed contexts. However, studies on ICQ in emerging economics, specifically the Middle East and North Africa region, which suffers from high levels of corruption, and asset misappropriation cases are limited. Hence, this work is important because it addresses under-researched issues in relation to ICQ in an attempt to develop a conceptual framework from the available and most effective organisational factors to attain better ICQ.